2000
DOI: 10.1002/hep.510310225
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of ELR+ to ELR− CXC chemokines affects the lung and liver injury following hepatic ischemia/reperfusion in the rat

Abstract: Hepatic ischemia/reperfusion (I/R) results in a neutrophildependent lung and liver injury. The process of neutrophil recruitment and activation in this injury is at least partially dependent on the presence of the ELR؉ CXC chemokines. Other investigations have shown that ELR؊ CXC chemokines can block ELR؉ CXC chemokine neutrophil recruitment and activation in vitro. To begin to investigate the role of the balance between these 2 types of molecules in vivo in neutrophil recruitment and activation following hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…Our data in IFNGR KO mice are consistent with reports in which IFN-deficient mice developed IR-mediated kidney and liver damage, comparable with WT. 12 However, others have shown that pharmacological doses of IFN-␥ may produce anti-inflammatory effects, 18 consistent with our finding that INFRG KO mice suffered even more severe IRI damage than WT. Indeed, IFN-␥ may exert cytoprotective functions by modulating the production of proteases/reactive oxygen species from KC, 19 by decreasing CD54 20 or E/P selectin 21 expression.…”
Section: Discussionsupporting
confidence: 91%
“…Our data in IFNGR KO mice are consistent with reports in which IFN-deficient mice developed IR-mediated kidney and liver damage, comparable with WT. 12 However, others have shown that pharmacological doses of IFN-␥ may produce anti-inflammatory effects, 18 consistent with our finding that INFRG KO mice suffered even more severe IRI damage than WT. Indeed, IFN-␥ may exert cytoprotective functions by modulating the production of proteases/reactive oxygen species from KC, 19 by decreasing CD54 20 or E/P selectin 21 expression.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, lymphocytes infiltrating hepatitis C-infected patients expressed CXCR3, and IP-10 was up-regulated on sinusoidal epithelium (10). In contrast, when IP-10 was elevated in response to IFN-␥ treatment, there was less injury in an ischemia-reperfusion model, as shown by a decrease in ALT values (12). Additionally, more recent data suggest that IP-10 expression correlates with a regenerative response in the liver (13).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of the non-ELR-CXC chemokines, including IFN-␥-inducible protein-10 (IP-10), monokine induced by IFN-␥, and IFNinducible T cell ␣ chemoattractant, which bind to CXCR3 and are inducible by the IFNs, are controversial in liver injury. While some studies have shown that IP-10 (also known as CXCL10) levels correspond to liver injury (10,11), IP-10 has been shown to have hepatoprotective effects (12), and recent studies have shown that its elevation correlates to the peak of DNA synthesis (13). Therefore, the aim of the current study was to elucidate the role of IP-10 during APAP-induced liver injury.…”
mentioning
confidence: 95%
“…Clinical observations of patients with acute respiratory distress syndrome (ARDS) and experimental studies on different animal models of lung injury have shown that sustained increases in pulmonary chemokines including IL-8, MIP-2, and CINC is a risk factor for the development of acute lung injury (17, 34 -37). Suppression of the ELR ϩ C-X-C chemokine (including MIP-2 and CINC) response has been shown to be associated with a significant decrease in lung injury irrespective of PMN influx in the lung in a rat model of hepatic ischemia and reperfusion (38). Although the inciting infection triggers the inflammatory cascade which serves to initiate an immune response, scavenging of soluble chemokines by the responding PMNs may be important in modulating the local host response.…”
Section: Discussionmentioning
confidence: 99%